2004
DOI: 10.1097/01.mlg.0000149444.30017.e8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Epidemiology of Hepatitis C Virus in Patients with Squamous Cell Carcinoma of the Head and Neck

Abstract: In this study, 21% of patients diagnosed with SCCHN were found to be infected with HCV. These patients presented at an earlier age but had similar presentation with respect to site and stage. More research is needed to determine the significance of HCV infection in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 6 publications
2
28
0
Order By: Relevance
“…A study conducted at a veterans administration medical centre in New Orleans reported that 21.2% of 99 patients with squamous cell carcinoma of the head and neck were co-infected with HCV, which was significantly higher than previously published data (9.9%) (P = 0.004) [114] . Contrarily, in another study from Japan assessing the prevalence of HCV in 4402 patients requiring oral surgery, HCV antibody was more prevalent in patients with oral cavity cancer than in those with impacted teeth (OR = 2.433; P = 0.05), but this difference was reversed after age adjustment (OR = 0.443; P = 0.05) [115] .…”
Section: Oral Squamous Cell Carcinomamentioning
confidence: 57%
“…A study conducted at a veterans administration medical centre in New Orleans reported that 21.2% of 99 patients with squamous cell carcinoma of the head and neck were co-infected with HCV, which was significantly higher than previously published data (9.9%) (P = 0.004) [114] . Contrarily, in another study from Japan assessing the prevalence of HCV in 4402 patients requiring oral surgery, HCV antibody was more prevalent in patients with oral cavity cancer than in those with impacted teeth (OR = 2.433; P = 0.05), but this difference was reversed after age adjustment (OR = 0.443; P = 0.05) [115] .…”
Section: Oral Squamous Cell Carcinomamentioning
confidence: 57%
“…The association between HCV infection and oral cavity cancer is still controversial [11], [12], [13]. HCV is a virus with triple tissue tropism – hepatotropism, lymphotropism, and sialotropism [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the transformation rate of oral lichen planus to OSCC is approximately 0.04% to 1.74% [31], [32]. Interestingly, Nobles et al demonstrated no predilection for the development of oral cavity cancers in patients infected with HCV [12]. Therefore, the role that HCV and its viral proteins play in the pathogenesis of oral diseases remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations